SiO2 / g-C3N4 embedded composite material as well as preparation method and application thereof

By growing SiO2 in situ on the pores of g-C3N4, SiO2/g-C3N4 mosaic composite material is formed, and the problems of low absorbance and slow charge transfer speed of photocatalyst composite material are solved, achieving efficient degradation of water pollutants.

CN119771470AActive Publication Date: 2025-04-08QILU UNIVERSITY OF TECHNOLOGY (SHANDONG ACADEMY OF SCIENCES)
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411992569.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-31
Publication Date
2025-04-08
Estimated Expiration
2044-12-31

AI Technical Summary

Technical Problem

When existing photocatalyst composites degrade water pollutants, there are problems such as low absorbance, high electron-hole recombination rate and slow charge transfer speed.

Method used

By growing SiO2 in situ on the pores of g-C3N4, SiO2/g-C3N4 mosaic composite material is formed, the electron-hole recombination rate is reduced, the charge transfer rate is increased, and the absorbance of the composite material is increased.

Benefits of technology

It effectively improves the photocatalytic degradation efficiency, significantly reduces the degradation time of dyes and antibiotics, and improves the degradation efficiency of pollutants.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119771470A_ABST
    Figure CN119771470A_ABST
Patent Text Reader

Abstract

The invention discloses a SiO2 / g-C3N4 embedded composite material as well as a preparation method and application thereof, and belongs to the technical field of photocatalysis. The SiO2 / g-C3N4 embedded type composite material is prepared from SiO2 microspheres and g-C3N4, wherein the SiO2 microspheres and the g-C3N4 are uniformly distributed; the g-C3N4 is of a lamellar porous structure; the SiO2 microspheres are embedded in the sheet layer and the surface of the g-C3N4 to form a tight interface bonding structure. According to the preparation method, SiO2 is grown on pores of g-C3N4 in situ, so that SiO2 microspheres are inlaid in the pores of g-C3N4, a SiO2 / g-C3N4 inlaid heterostructure is formed, the electron-hole recombination rate can be reduced, the transfer rate of charges to the surface of a material is increased, the problem that the process of transferring the charges to the surface of the material is relatively slow is solved, and the performance of the material is improved. And the absorbance is much higher than that of pure substances. The SiO2 / g-C3N4 embedded composite material can be used for effectively degrading RhB, methylene blue and tetracycline hydrochloride in photocatalytic degradation water treatment.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the field of photocatalysis technology and specifically relates to a SiO 2 / gC 3 N 4 Inlay composite material and preparation method and application thereof. Background Art

[0002] The information disclosed in this background technology section is only intended to enhance the understanding of the overall background of the invention, and should not necessarily be regarded as an admission or any form of suggestion that the information constitutes the prior art already known to a person skilled in the art.

[0003] Water pollution is recognized as one of the most serious problems in the world. In order to solve this problem, many methods have been adopted, among which photocatalytic degradation has received widespread attention. However, there are still some problems with photocatalytic degradation of dyes, such as low photocatalytic degradation efficiency, poor stability, and low sustainable utilization rate. These problems are mainly caused by the low absorbance of photocatalyst composite materials, high electron-hole recombination rate, and slow charge transfer to the material surface. Summary of the invention

[0004] In order to solve the deficiencies of the prior art, the present invention aims to provide a SiO 2 / gC 3 N 4 Mosaic composite material and preparation method and application thereof, the present invention is through gC 3 N 4 In-situ growth of SiO 2 , making SiO 2 Nanospheres embedded in gC 3 N 4 In the pores, a SiO 2 / gC 3 N 4 The mosaic heterostructure can reduce the electron-hole recombination rate and increase the rate of charge transfer to the material surface, thereby solving the problem of slow charge transfer to the material surface, and its absorbance is much higher than that of pure substances.

[0005] In order to achieve the above object, the technical solution of the present invention is:

[0006] In a first aspect, the present invention provides a SiO 2 / gC 3 N 4 Mosaic composite material, composed of SiO 2 Microspheres and gC 3 N 4 Composition: said gC 3 N4 Having a lamellar porous structure; the SiO 2 Microspheres embedded in gC 3 N 4 layers and surfaces to form a tight interface bonding structure.

[0007] SiO 2 The average particle size of the microspheres is 1-5 microns.

[0008] It is understood that the term "embedded" refers to a portion of the 3 N 4 Inside the interlayer, part of it is exposed on gC 3 N 4 The surface of the mosaic is gC 3 N 4 In-situ growth of SiO in the pores of the sheets 2 , making SiO 2 Rooted in gC 3 N 4 In the pores, a mosaic effect is achieved.

[0009] Preferably, SiO 2 and gC 3 N 4 The mass ratio is 1:(1-4), preferably 1:(2-3).

[0010] In a second aspect, the present invention provides the SiO 2 / gC 3 N 4 The preparation method of the mosaic composite material comprises the following steps:

[0011] C 3 N 4 The mixture is dispersed in an alcohol aqueous solution, and ammonia water and tetraethyl silicate (TEOS) are added in sequence and stirred to obtain a mixed solution, which is centrifuged, washed, and dried to obtain a mixed material, and the mixed material is calcined at high temperature to obtain SiO 2 / gC 3 N 4 Inlay composite material.

[0012] In one or more embodiments, the gC 3 N 4 In order to use melamine as a precursor, gC with pores was obtained by high temperature calcination in a closed reactor. 3 N 4 .

[0013] Preferably, the calcination temperature is 590-610°C, the calcination time is 3-4h, and the heating rate and cooling rate are both 5°C / min.

[0014] In one or more embodiments, in the alcohol-water solution, the alcohol is ethanol, methanol, isopropanol or butanol, preferably ethanol, and the volume ratio of alcohol to water is (6-8):1.

[0015] In one or more embodiments, gC 3 N 4 The feeding ratio of alcohol aqueous solution, ammonia water and tetraethyl silicate (TEOS) is (1-4g):(70-90mL):(2-4mL):(3-4mL), preferably (1-4g):80mL:3mL:3.5mL.

[0016] In one or more embodiments, the dispersion is carried out by ultrasonic dispersion, and the ultrasonic time is 5-20 min.

[0017] In one or more embodiments, after adding ammonia water, stirring is carried out at room temperature for 5-20 minutes; after adding tetraethyl silicate (TEOS), stirring is carried out at room temperature for 6-10 hours.

[0018] In one or more embodiments, the centrifugal speed is 5000-8000 r / min, and the centrifugal time is 3-6 minutes.

[0019] In one or more embodiments, the washing is performed multiple times using water.

[0020] In one or more embodiments, the drying temperature is 100-125° C., and the drying time is 3-6 hours.

[0021] In one or more embodiments, the calcination temperature is 500-600° C., the calcination time is 0.5-1.5 h, and the heating rate is 3-6° C. / min, preferably 5° C. / min.

[0022] In a third aspect, the present invention provides the SiO 2 / gC 3 N 4 Application of mosaic composite materials in photocatalytic degradation water treatment.

[0023] Preferably, the water treatment is to degrade water containing dyes and / or antibiotics.

[0024] Preferably, the dye comprises one or more of methylene blue, rhodamine B or methyl orange.

[0025] Preferably, the antibiotics include one or more of tetracycline hydrochloride, oxytetracycline, doxycycline and chlortetracycline.

[0026] In a fourth aspect, the present invention provides a method for photocatalytic degradation of water, comprising the following steps:

[0027] The above SiO2 / gC 3 N 4 The mosaic composite material is added to the water to be treated as a photocatalyst and photocatalytically degrades the water under the irradiation of visible light.

[0028] The water to be treated is water containing dyes and / or antibiotics.

[0029] One or some of the above technical solutions have the following advantages or beneficial effects:

[0030] (1) The present invention provides a SiO 2 / gC 3 N 4 Mosaic composite materials, through gC 3 N 4 In-situ growth of SiO in the pores 2 , making SiO 2 Nanospheres embedded in gC 3 N 4 In the pores, a SiO 2 / gC 3 N 4 The mosaic heterostructure can reduce the electron-hole recombination rate, increase the charge transfer rate to the material surface and improve the absorbance of the composite material, solving the problems of low absorbance of photocatalyst composite materials, high electron-hole recombination rate and slow charge transfer to the material surface.

[0031] (2) SiO provided by the present invention 2 / gC 3 N 4 The mosaic composite material can effectively degrade dyes and / or antibiotics (such as RhB, methylene blue and tetracycline hydrochloride) in photocatalytic degradation of water. In the photocatalytic degradation of RhB experiment, 94% of the degradation was achieved in 15 minutes; in the photocatalytic degradation of methylene blue and tetracycline hydrochloride, the degradation effects of the two reached 90% and 85% respectively in about 180 minutes. Obviously, the SiO 2 / gC 3 N 4 Mosaic composite materials as photocatalysts can effectively improve the degradation efficiency of pollutants and are beneficial to the treatment of water pollution.

[0032] (3) The present invention provides a new type of SiO 2 / gC 3 N 4 The morphology and structure of the composite material are achieved through a specific synthesis method to achieve a mosaic effect, and SiO 2 and gC 3 N4 The interface bonding is very tight, which is conducive to the transfer of interface electrons. BRIEF DESCRIPTION OF THE DRAWINGS

[0033] The accompanying drawings in the specification, which constitute a part of the present invention, are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute improper limitations on the present invention.

[0034] Figure 1 The SiO prepared in Example 2 of the present invention 2 / gC 3 N 4 SEM images of the mosaic composite material at different magnifications; (a) and (b) are at magnifications of 6k and 18k, respectively;

[0035] Figure 2 gC prepared in Comparative Example 2 of the present invention 3 N 4 The morphology of the image; the magnification is 8k;

[0036] Figure 3 The SiO prepared in Example 2 of the present invention 2 / gC 3 N 4 Absorption characteristics of UV-visible diffuse reflectance spectrum and transient photocurrent intensity diagram of embedded composite materials; wherein a is the absorption characteristics of UV-visible diffuse reflectance spectrum, and b is the transient photocurrent intensity diagram;

[0037] Figure 4 This is a degradation efficiency diagram of the photocatalytic degradation of RhB solution in Application Example 1 of the present invention;

[0038] Figure 5 This is a degradation efficiency diagram when photocatalytic degradation of methylene blue and tetracycline hydrochloride solution is performed in Application Example 2 of the present invention. DETAILED DESCRIPTION

[0039] In order to enable those skilled in the art to more clearly understand the technical solution of the present invention, the technical solution of the present invention will be described in detail below in conjunction with specific embodiments.

[0040] All reagents and drugs in the present invention can be purchased from commercial sources.

[0041] Example 1

[0042] 1. gC 3 N 4 Preparation:

[0043] 20 g of melamine was put into a ceramic crucible and placed in a muffle furnace. The heating rate and cooling rate were set to 5 °C / min, and the calcination temperature was 600 °C for 3 h. After the crucible was naturally cooled to room temperature, the sample was taken out to obtain gC with pores. 3 N 4 , gC 3 N 4 Grind in a mortar and collect for later use.

[0044] 2. Preparation of composite materials:

[0045] Take 1g of prepared gC 3 N 4 Add to the beaker, add 70mL of 2 H 5 OH and 10mLH 2 O and put the beaker into ultrasonic cleaning machine for 10 minutes to make gC 3 N 4 After uniform dispersion, add 3 mL of ammonia water and stir with a magnetic bar at a constant temperature of 25°C for 10 minutes. Finally, add 3.5 mL of TEOS and continue stirring at a constant temperature of 25°C for 9 hours to obtain a mixed solution. The obtained mixed solution was placed in a centrifuge at a centrifugal speed of 7000 r / min for 5 minutes. The obtained product was rinsed with deionized water and repeated 3-4 times. The product was then placed in a 120°C oven and dried for 4 hours to obtain SiO 2 / gC 3 N 4 Finally, the mixed material was placed in a muffle furnace and calcined at 550°C for 1h to obtain the composite material SCN-1.

[0046] Example 2

[0047] The difference from Example 1 is that gC 3 N 4 The added amount was 2 g, and the obtained composite material was SCN-2.

[0048] Example 3

[0049] The difference from Example 1 is that gC 3 N 4 The added amount is 3 g, and the obtained composite material is SCN-3.

[0050] Example 4

[0051] The difference from Example 1 is that gC 3 N 4 The added amount is 4 g, and the obtained composite material is SCN-4.

[0052] Comparative Example 1

[0053] SiO 2 Preparation:

[0054] Add 70 mL of 2 H 5 10 mL of OH water was added to stir it evenly, then 3 mL of ammonia water was added and stirred with a magnetic bar at a constant temperature of 25°C for 10 min, and finally 3.5 mL of TEOS was added. The prepared solution was placed in a water bath at 25°C and stirred for 9 h. Finally, SiO 2 The obtained SiO 2 The solution was placed in a centrifuge at a speed of 7000 r / min for five minutes. The obtained product was rinsed with deionized water and repeated 3-4 times. The product was then placed in a 120°C oven and dried for 4 hours to obtain the final product 1g SiO 2 , grind it in a mortar and collect it for later use. 2 The average particle size is 2 microns.

[0055] Comparative Example 2

[0056] C 3 N 4 Preparation:

[0057] A certain amount of melamine was put into a ceramic crucible and placed in a muffle furnace. The heating rate and cooling rate were set to 5°C / min, and the calcination temperature was 600°C for 3 hours. After the crucible was naturally cooled to room temperature, the sample was taken out to obtain gC with pores. 3 N 4 , gC 3 N 4 Grind in a mortar and collect for later use.

[0058] Comparative Example 3

[0059] Different from Example 1, TEOS and gC 3 N 4 The order of addition was adjusted, that is, TEOS was added first and gC was added last. 3 N 4 The prepared composite material cannot form a mosaic composite material, but can only realize SiO 2 Load in gC 3 N 4 surface.

[0060] Comparative Example 4

[0061] Patent CN107649177A embodiment 1 specifically includes the following steps:

[0062] (1) 30 g of melamine was placed in a tube furnace and calcined at 500 °C for 4 h in an air atmosphere to obtain gC 3 N 4 .

[0063] (2) Mix 8 mL of ethyl silicate and 40 mL of anhydrous ethanol, and add 1 g of gC prepared in the above step. 3 N 4 , to prepare mixed solution A; add 6mL of 1mol / L HNO 3 , 2 mL of 3% HF and 12 mL of anhydrous ethanol were mixed to prepare mixed solution B; mixed solution B was added to mixed solution A while stirring to form a sol; the sol was transferred into a reaction kettle and subjected to hydrothermal synthesis at 100°C. After reacting for 24 hours, the cooled product was separated by filtration, and the separated solid matter was washed and dried to obtain gC 3 N 4 / SiO 2 Photocatalyst.

[0064] The gC obtained in this comparative example 3 N 4 / SiO 2 The photocatalyst is not a mosaic type composite.

[0065] Depend on Figure 2 It can be seen that in Example 1 of the present invention and Comparative Example 2, gC with pores was prepared. 3 N 4 .

[0066] Depend on Figure 1 It can be seen that the SiO prepared by the present invention 2 / gC 3 N 4 The mosaic composite material achieves a mosaic effect, in which SiO 2 The nanospheres are densely embedded in gC 3 N 4 surface, and it can be seen from the figure that SiO 2 and gC 3 N 4 The interface bonding is very tight, which is conducive to the transfer of interface electrons.

[0067] Depend on Figure 3 From the a in the equation, we can see that it is the same as the pure substance gC 3 N 4 and SiO 2In comparison, the absorption characteristics of the composite material are significantly enhanced, which indicates that the formed mosaic heterostructure can improve the light absorption capacity of the composite material in the ultraviolet and visible regions. The weakening of the absorption characteristics of SCN-1 may be due to the large proportion of silica, which accumulates on the surface of the composite material, affecting the composite material's absorption of light to a certain extent.

[0068] from Figure 3 As can be seen from b in the figure, compared with pure substance gC 3 N 4 The transient photocurrent intensity of the composite SCN is significantly enhanced. Among them, the transient photocurrent of SCN-2 is significantly higher than that of other samples, which may be due to the most suitable ratio resulting in a larger specific surface area and SiO 2 The good charge transfer properties of the nanospheres and their dense embedding in gC 3 N 4 The surface increases more active sites, reduces the barrier of electron transfer, and shortens the path of electron transfer, thereby inhibiting the recombination of photogenerated carriers.

[0069] Application Example 1 Photocatalytic degradation of RhB solution:

[0070] Prepare 20 mg / L RhB solution, take 100 mL of RhB solution for each test and add 0.1 g of photocatalyst (including the catalyst prepared in Examples 1-4, SiO prepared in Comparative Example 1) 2 And the gC prepared in Comparative Example 2 3 N 4 ). At a wavelength of 554 nm, based on the absorbance value corresponding to this wavelength, the degradation results are as follows Figure 4 As shown. Figure 4 It can be clearly seen that the degradation of RhB dye can reach about 95% in 15 minutes.

[0071] Application Example 2 Photocatalytic degradation of tetracycline hydrochloride and methylene blue:

[0072] 30 mg / L methylene blue solution and tetracycline hydrochloride solution were prepared respectively. 100 mL of methylene blue solution and tetracycline hydrochloride solution were added with 0.1 g of photocatalyst (the photocatalyst was SCN-2 prepared in Example 2) for each test. The methylene blue solution was at a wavelength of 665 nm and the tetracycline hydrochloride was at a wavelength of 358 nm. Based on the absorbance values ​​corresponding to the wavelengths, the degradation results are as follows: Figure 5 As shown in the figure, it can be seen that the degradation effects of the two reached 90% and 85% at around 180 minutes.

[0073] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A SiO2 / g-C3N4 mosaic composite material, characterized in that: It consists of SiO2 microspheres and g-C3N4; the g-C3N4 has a lamellar porous structure; the SiO2 microspheres are embedded in the lamellar layers and surface of the g-C3N4 to form a tight interface bonding structure.

2. The SiO2 / g-C3N4 mosaic composite material according to claim 1, characterized in that: The mass ratio of SiO2 microspheres to g-C3N4 is 1:(1-4), preferably 1:(2-3).

3. A method for preparing the SiO2 / g-C3N4 mosaic composite material according to claim 1 or 2, characterized in that: The following steps are involved: g-C3N4 is dispersed in an alcohol aqueous solution, and ammonia water and ethyl silicate are added in sequence and stirred to obtain a mixed solution, which is centrifuged, washed, and dried to obtain a mixed material, and the mixed material is calcined at high temperature to obtain a SiO2 / g-C3N4 mosaic composite material.

4. The preparation method according to claim 3, characterized in that: The g-C3N4 is prepared by calcining melamine as a precursor in a closed reactor at a high temperature to obtain g-C3N4 with pores; Preferably, the calcination temperature is 590-610° C., the calcination time is 3-4 h, and the heating rate and cooling rate are both 5° C. / min.

5. The preparation method according to claim 3, characterized in that: In the alcohol aqueous solution, the alcohol is ethanol, methanol, isopropanol or butanol, preferably ethanol; Preferably, the volume ratio of alcohol to water is (6-8):1; Preferably, the feed ratio of g-C3N4, alcohol aqueous solution, ammonia water and ethyl silicate is (1-4g):(70-90mL):(2-4mL):(3-4mL), preferably (1-4g):80mL:3mL:3.5mL.

6. The preparation method according to claim 3, characterized in that: The dispersion is carried out by ultrasonic dispersion, and the ultrasonic time is 5-20 minutes; Preferably, after adding ammonia water, stirring is carried out at room temperature for 5-20 minutes; Preferably, after adding ethyl silicate, stirring is carried out at room temperature for 6-10 hours.

7. The preparation method according to claim 3, characterized in that: The centrifugal speed is 5000-8000r / min, and the centrifugal time is 3-6 minutes; Preferably, the drying temperature is 100-125°C and the drying time is 3-6h; Preferably, the calcination temperature is 500-600°C, the calcination time is 0.5-1.5h, and the heating rate is 3-6°C / min.

8. Use of the SiO2 / g-C3N4 mosaic composite material according to claim 1 or 2 or the SiO2 / g-C3N4 mosaic composite material obtained by the preparation method according to any one of claims 3 to 7 in photocatalytic degradation water treatment.

9. The use according to claim 8, characterized in that: The water treatment is to degrade water containing dyes and / or antibiotics; Preferably, the dye comprises one or more of methylene blue, rhodamine B and methyl orange; Preferably, the antibiotics include one or more of tetracycline hydrochloride, oxytetracycline, doxycycline and chlortetracycline.

10. A method for photocatalytic degradation of water treatment, characterized in that: The following steps are involved: Adding the SiO2 / g-C3N4 mosaic composite material as claimed in claim 1 or 2 into the water to be treated as a photocatalyst, and performing photocatalytic degradation under the irradiation of visible light; The water to be treated is water containing dyes and / or antibiotics.

Citation Information

Patent Citations

  • Preparation method of C3N4 / SiO2 heterojunction photocatalyst

    CN106391086A

  • Embedded-structure ZnO#SiO2 nanoparticle preparation method and product and application thereof

    CN108654593A

  • Graphite carbon modified silicon dioxide-carbon nitride core-shell nanosphere material, graphene oxide-based composite film and preparation method and application of graphite carbon modified silicon dioxide-carbon nitride core-shell nanosphere material and graphene oxide-based composite film

    CN117399042A

  • Preparation method for hollow nitrogen-doped carbon-coated titanium dioxide photocatalyst

    WO2023241152A1